2018 IEEE 59th Annual Symposium on Foundations of Computer Science (FOCS) 2018
DOI: 10.1109/focs.2018.00058
|View full text |Cite
|
Sign up to set email alerts
|

Perfect Lp Sampling in a Data Stream

Abstract: In this paper, we resolve the one-pass space complexity of perfect L p sampling for p ∈ (0, 2) in a stream. Given a stream of updates (insertions and deletions) to the coordinates of an underlying vector f ∈ R n , a perfect L p sampler must output an index i with probability |f i | p / f p p , and is allowed to fail with some probability δ. So far, for p > 0 no algorithm has been shown to solve the problem exactly using poly(log n)-bits of space. In 2010, Monemizadeh and Woodruff introduced an approximate L p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 48 publications
0
44
0
Order By: Relevance
“…Considering the results of [51], this resolves the space complexity of L p sampling for p ∈ (0, 2). For p = 2, the space complexity of [46] is O(log 3 n log(1/δ )) which matches the space of the best approximate sampler without dependence on ε.…”
Section: Canonical L P Sampling Algorithmmentioning
confidence: 88%
See 1 more Smart Citation
“…Considering the results of [51], this resolves the space complexity of L p sampling for p ∈ (0, 2). For p = 2, the space complexity of [46] is O(log 3 n log(1/δ )) which matches the space of the best approximate sampler without dependence on ε.…”
Section: Canonical L P Sampling Algorithmmentioning
confidence: 88%
“…Perfect L p Sampling. Recently, Jayaram and Woodruff [46] extended this approach to show space efficient perfect L p samplers. In other words, for p ∈ (0, 2) they give L p samplers with zero error in the sampling distribution (∆ = 0, ε = 0) using only O(log 2 n log(1/δ )) space.…”
Section: Canonical L P Sampling Algorithmmentioning
confidence: 99%
“…When β ≥ 1 is not an integer, x −β is interpreted as x −⌊β⌋ . We will need the following lemma which bounds the tail ℓ 2 and ℓ 1 norm of a vector after its entries are scaled independently by random variables Lemma 5.6 (Generalization of Proposition 1 of [JW21]). Fix n ∈ AE and c ≥ 0, and let D 1 , .…”
Section: Independently and Outputmentioning
confidence: 99%
“…Theorem 10 (Perfect ℓ 1 -sampling [JW21]). For m ∈ AE, let c > 1 be an arbitrarily large constant and t = O(log 2 m).…”
Section: Count-sketch ℓ 1 -Sketch and ℓ 1 -Samplingmentioning
confidence: 99%
“…A sequence of works showed that it is possible to compute a linear sketch of X that allows one to perform approximate L p sampling [17]. Such sketches can be used to perform moment estimation [45,54] and entropy estimation [13]. L 0 sampling is used for graph sketching, as discussed below.…”
Section: Background On Sketchingmentioning
confidence: 99%